2010
DOI: 10.1111/j.1742-1241.2010.02370.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of extended-release niacin/laropiprant plus statin vs. doubling the dose of statin in patients with primary hypercholesterolaemia or mixed dyslipidaemia

Abstract: Summary Background:  Co‐administration of niacin with statin offers the potential for additional lipid management and cardiovascular risk reduction. However, niacin is underutilised because of the side effects of flushing, mediated primarily by prostaglandin D2 (PGD2). A combination tablet containing extended‐release niacin and laropiprant (ERN/LRPT), a PGD2 receptor (DP1) antagonist, offers improved tolerability. This study assessed the efficacy and safety of ERN/LRPT added to statin vs. doubling the dose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…190 -192 Combination of niacin with laropiprant, an inhibitor of the prostaglandin D 2 receptor, 193 significantly reduced but did not abolish flushing, the main tolerability issue. Among patients with T2DM, transient impairment of glucose control was reported (median increase in HbA 1C 0.3% over 12 weeks), 194,195 consistent with known effects with niacin. 188,189 Emerging evidence suggests that statin plus niacin can reduce progression of atherosclerosis in high-risk patients, including those with low LDL-C, as in the Oxford Niaspan trial 182 (Supplementary material online, Table S1).…”
Section: -173mentioning
confidence: 62%
“…190 -192 Combination of niacin with laropiprant, an inhibitor of the prostaglandin D 2 receptor, 193 significantly reduced but did not abolish flushing, the main tolerability issue. Among patients with T2DM, transient impairment of glucose control was reported (median increase in HbA 1C 0.3% over 12 weeks), 194,195 consistent with known effects with niacin. 188,189 Emerging evidence suggests that statin plus niacin can reduce progression of atherosclerosis in high-risk patients, including those with low LDL-C, as in the Oxford Niaspan trial 182 (Supplementary material online, Table S1).…”
Section: -173mentioning
confidence: 62%
“…Adding ERN/LRPT to statin has been shown to have a greater effect than doubling statin dose in improving lipid profile (LDL-C, -10 vs -5.5%; HDL-C, 15.8 vs 0.2%; TGL, -17.6 vs -4%; apoB, -10.7 vs -2.4%; apoA1, 6.9 vs 1% and Lp (a), -18.2 vs 0%; p < 0.001 for all) [102]. In the same study, [104].…”
Section: Postmarketing Studiesmentioning
confidence: 91%
“…Approximately 6000 patients have participated in many studies focusing on safety of ERN/LRPT combination compared with ERN, statins or placebo [50,85,101,102,121]. The outcomes suggest that the combination of ERN and LRPT is as safe as ERN alone [55] but there is no long-term data on the safety of LRPT.…”
Section: Safety Evaluation Of Ern/lrpt In Clinical Trialsmentioning
confidence: 99%
“…Prior studies have shown that ERN LRPT improves key lipid parameters associated with increased CHD risk in patients with primary hypercholesterolemia or mixed dyslipidemia. [12][13][14][15] CHD risk may vary among different patient subgroups, including sex, race, and age. [16] CHD risk may also differ among patients based on their lipid levels, use of statin therapy, CHD risk category, and type of hyperlipidemia.…”
Section: Introductionmentioning
confidence: 99%